O-005 New cone beam CT assessment of acute stroke patients: are we ready for prime time?. (22nd July 2018) - Cancelliere, N; Grunhagen, T; Bracken, J; Nijnatten, F; Krings, T; Pereira, V Mendes
Abstract : Introduction: Large vessel occlusions have been successfully treated with mechanical thrombectomy in recent years. Reducing the time between symptom onset and revascularization has the potential to significantly improve patient's outcome. As intrahospital transfer from CT to the angiosuite can delay revascularization therapy by up to 60 min, recent cone-beam CT based stroke imaging software for the angiosuite has been developed in an attempt to create a 'one-stop-shop stroke suite' in angio. The purpose of this study is to evaluate this stroke imaging acquired in the angiosuite and compare to standard CT. Materials and methods: We included in this study patients who received endovascular mechanical thrombectomy (EVT) treatment that performed standard CT and CT perfusion (CTP) imaging within 90 min before arrival to the angiosuite. Upon arrival, patients were imaged using two unique conebeam CTs: 1) a non-enhanced XperCT 'mask' image, followed by 2) a dual-phase (DP) IV contrast enhanced XperCT. Fluoroscopy was used to determine arrival of contrast in the circle of willis and initiate the DP scans. DP scans provide volumetric images of two phases referred to as 'early' and 'late' brain perfusion phases. The specialized stroke analysis software (Philips, Best) then performs a subtraction of these two phases to highlight brain regions of delayed filling. Using a 5-point quality assessment questionnaire, the perfusion XperCT imaging acquired in the angio-suite was evaluated by an experienced interventional neuroradiologist and compared to previously acquired standard CT and CTP imaging and follow-up CT imaging acquired 24 hours later. Results: We included currently 20 patients. Preliminary results demonstrated that the XperCT stroke imaging software in the angiosuite sufficiently provides the necessary diagnostic information required for treatment decision-making, including detection of ischemic core (ASPECTS score), collaterals (good, moderate or bad) and vessel patency (occluded vessel and baseline TIMI). More specifically, core definition compared to baseline CT, CT perfusion and follow-up CT demonstrated good predictability of the final infarct in cases with complete revascularization in less than 60 min after baseline imaging. Data analysis and statistics will be presented at the conference as well as images examples for comparison and illustration. Conclusion: Currently, stroke patients must first visit the CT department for imaging to confirm LVO before going to the angiography suite for EVT treatment. Preliminary results from analysis of this cone-beam CT assessment suggests that in the future eligible patients can bypass CT and go straight to the angiosuite for imaging and treatment. Disclosures: N. Cancelliere: None. T. Grunhagen: 5; C; Philips. J. Bracken: 5; C; Philips. F. Nijnatten: 5; C; Philips. T. Krings: None. V. Mendes Pereira: 1; C; Philips.